2013
DOI: 10.1002/jor.22324
|View full text |Cite
|
Sign up to set email alerts
|

Serum cartilage oligomeric matrix protein (COMP) in knee osteoarthritis: A novel diagnostic and prognostic biomarker

Abstract: A case-control study was conducted to estimate the association of cartilage oligomeric matrix protein (COMP) with knee osteoarthritis (OA) and to examine the potential utility of COMP as a diagnostic and prognostic biomarker in early knee OA. The COMP levels were estimated in the blood sera of 150 subjects belonging to study group (n ¼ 100) and control one (n ¼ 50). Patients with confirmed clinical isolated knee OA diagnosed through American College of Rheumatology criteria were included and were without any o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 37 publications
5
107
1
Order By: Relevance
“…14 In turn, IL-1b has been shown to be correlated with serum COMP levels in OA and Kashin-Beck disease. 15,16 Possibly downstream IL-1b-mediated inflammation is responsible for cartilage degradation/regeneration and rise in serum COMP levels. By stabilizing the inflammasome pathway, colchicine may be acting as a diseasemodifying agent in OA.…”
Section: Discussionmentioning
confidence: 99%
“…14 In turn, IL-1b has been shown to be correlated with serum COMP levels in OA and Kashin-Beck disease. 15,16 Possibly downstream IL-1b-mediated inflammation is responsible for cartilage degradation/regeneration and rise in serum COMP levels. By stabilizing the inflammasome pathway, colchicine may be acting as a diseasemodifying agent in OA.…”
Section: Discussionmentioning
confidence: 99%
“…OA can be triggered by various factors like inflammation, physical injury, and other metabolic causes [2]. A number of environmental risk factors such as obesity and trauma can also initiate diverse pathological pathways which may eventually lead to OA [3]. …”
Section: Introductionmentioning
confidence: 99%
“…The authors have suggested that high levels of COMP and HA might predict incident radiographic knee OA. According to the results of another survey, serum COMP levels were found to be correlated with the risk of rapidly progressing OA and to be remained significantly high in first 3 years of disease duration (15). All these findings suggest that serum COMP levels may be a useful assessment tool for OA.…”
Section: Cartilage Oligomeric Matrix Proteinmentioning
confidence: 93%